Critiquing the Most Congenial of Lives: The Rise of the Canadian Academic Novel - Bajwa, Poonam (University of Ottawa (Canada), 2010)
Focusing on a selection of pioneering works, which include Margaret Atwood's The Edible Woman (1969), Robert Kroetsch's Gone Indian (1973), Robertson Davies's The Rebel Angels (1981), and Carol Shields's Swann (1987), this dissertation traces the uncharted emergence and development of the Canadian academic novel and argues that it should be recognized alongside its already well-documented American and British counterparts as constituting a significant contribution to the sub-genre. The novels under consideration, published between 1969 and 1987, directly respond to the contemporaneous growth and expansion of the Canadian university as well as, in light of this expansion, its resultant growing pains: in this saturated academic climate, producing unique scholarship that would both secure the individual's professional status as well as contribute to the broader public in a discernable fashion became increasingly difficult. In response, these novelists, whose works are set primarily in English departments, target the scholar's tendency to prioritize professional self-interest above scholarly idealism rather than strike a productive balance between the two. Entering into an ongoing dialogue about the value of humanities (particularly literary) scholarship, they ultimately suggest that when alternative models of scholarly inquiry are adopted in place of standard paradigms and the disinterested pursuit of knowledge remains the foundational guiding principle, the resulting research has the potential to offer invaluable insights with broader cultural and social resonances.
Keywords: Literature, Canadian (English).